Causal Relationship Between Gut Microbiota and Leukemia: Future Perspectives - Qiang Yang; Zexin Wang; Miao Liu; Lingling Gan (Oncology and Therapy)
Abstract The gut microbiota plays a crucial role in maintaining homeostasis in the human gastrointestinal tract. Numerous studies have shown a strong association between the gut microbiota and the emergence and progression of various diseases. Leukemia is one of the most common hematologic malignancies. Although standardized protocols and expert consensus have been developed for routine diagnosis and treatment, limitations remain due to individual differences. Nevertheless, a large number of studies have established a link between the gut microbiota and leukemia, with disturbances in the gut microbiota directly or indirectly affecting the development of leukemia. However, the causal relationship between the two remains unclear, and studying and exploring the causal relationship may open up entirely new avenues and protocols for use in the prevention and/or treatment of leukemia, offering new insights into diagnosis and treatment. In this review, the intricate relationship between the gut microbiota and leukemia is explored in depth, including causal associations, metabolite effects, therapeutic applications, and complications. Based on the characteristics of the gut microbiota, the future applications and prospects of gut microbiota are discussed to provide useful information for clinical treatment of leukemia.